Breast Cancer Survivors' Preferences and Barriers Related to ICT-Based Diet and Physical Activity Interventions. (7th June 2021) - Chen, X; Chiu, C; Cheung, HT; White, ME; Chen, X; Trinh, L; Arthur, AE
Abstract: Objectives: To establish the preferences and perceived barriers related to physical activity and diet programming of breast cancer survivors (BCS) to inform the development of Information and Communication Technology (ICT)-based lifestyle interventions. Methods: This was a cross-sectional study of 197 BSC aged 18 years or older and diagnosed with ductal carcinoma in situ (DCIS) or Stage I-IV breast cancer. The BCS were recruited during routine oncology appointments at a Midwestern cancer center. A survey was conducted to query survivors' level of interest in, preferences for, and perceived barriers to participating in an exercise and dietary intervention program, with a specific emphasis on ICT-based programming. Results: Overall, 85% of BCS reported they would consider participating in exercise and diet intervention research. Approximately 45% of participants reported that they had received diet and/or exercise information as part of their cancer care. However, only 15% of the participants received such information from healthcare professionals with the appropriate expertise (e.g., Dietitian, Exercise Specialist). Over two-thirds of the participants reported frequent use of mobile devices and the internet, and 80% indicated comfort using these devices (e.g., tablet, smart phone). The top three preferred formats for an ICT-based diet and exercise intervention program were "website", "mobile apps" and "e-mails". Older participants (>60 years) were more likely to report a preference for e-mails while younger participants (<60 years) were more likely to report a preference for websites or mobile apps. The most common perceived barriers to participation in a lifestyle intervention included fatigue, family responsibility and work. Conclusions: Most BCS in this study were interested in exercise and diet interventions and would be comfortable with an ICT-based format with a preference for delivery via websites, mobile apps or e-mails. Future ICT-based lifestyle interventions should be designed with consideration of BCS' age, barriers, facilitators and other characteristics. Funding Sources: USDA-NIFA Hatch Project 1, 011, 487